Acute Toxicity Effect of Aqueous Extract of Stem Bark of Diospyrus Mespiliformis on Kidneys and Biochemical Parameters of WistarRats - Muhammad, A.T. , Bukkuyum, K.B. , Mohammed, M.O.* ., Abubakar, U. , Avwioro, O.G. , 1 1 1 Mohammed, I. , Ajayi, A.S. , Usman, K (Sokoto Journal of Medical Laboratory Science)
Acute Toxicity Effect of Aqueous Extract of Stem Bark of Diospyrus Mespiliformis on Kidneys and Biochemical Parameters of WistarRats